Optimalisasi Peran Kepala Madrasah sebagai Supervisor melalui Metode Mentoring di MTs N Ngemplak dan MTs Ummul Quro Kabupaten Sleman tahun 2016 - Charisatuniswah Charisatuniswah (Jurnal Pendidikan Madrasah, 2018)
One of the roles of the head of the madrasa is as supervisors, i.e. carry out supervision of the implementation of the learning to the teacher with the aim of helping to improve competencies in learning activities with a tangible, measurable program, controlled, directional to achieve learning objectives. To view the role of head of the madrasa, this research aims to know (1) how the implementation of the role of head of the madrasa as a supervisor at MTsN Ngemplak, and MTs Ummul Quro; (2) Optimizing the role of head of the madrasa as a supervisor through mentoring in MTsN Ngemplak, and MTs Ummul Quro. This research uses research methods of action. Implemented on 1st October-April 1, 2016, using methods of mentoring that was implemented in three cycles. Data collection by using the observation, interview, and documentation. Procedure actions 1) planning, 2) supervision of the implementation of action, 3) observation, and 4) reflection. The results showed that optimizing the role of head of the madrasa as a supervisor through the mentoring method is implemented through three cycles have been successfully delivering a positive impact and has increased both in terms of planning, implementation, assessment or follow-up on the implementation of its role as a supervisor. This is evidenced by the existence of the data observations from the initial findings prior to the implementation of mentoring for MTsN Ngemplak was 63.75% and after the mentoring for 3 cycles then retrieved the value of observations 97.50%. So there is a growing method of mentoring with 33.75%. Whereas in MTs Ummul Quro, the initial findings of the observation value obtained 57.50%. Mentoring results results for 3 cycles obtained the value 87.50% observation results. So there is an increase of 30%.